Introduction of the system of professional liability insurance for medical workers in Kazakhstan: issues of formation of the legislative framework - Aytkazin, Е.М.; Kaishatayeva, А.К.; Muratkhanova, М.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article analyzes the legal basis of the system of professional liability insurance of medical workers being implemented in the Republic of Kazakhstan. The system of professional liability insurance of medical workers is a new and ambitious project, the legislative basis of which is at the stage of formation and requires additional theoretical and scientific research. In accordance with the current legislation - a doctor no longer has the right to carry out medical activities without concluding a contract of professional liability insurance for medical workers. That is, this type of insurance has become mandatory and this, according to the authors, will have a positive impact on the quality of medical services. According to the authors, the introduction of this system in the Republic of Kazakhstan should facilitate the payment of compensation to injured patients, protect the medical worker in case of inadvertent error and strengthen the legal status of the doctor in the domestic health care system. The introduction of professional liability insurance for medical workers facilitates interaction between the patient, the doctor and the medical organization. Patients will not need to go to court with a claim for damages under civil liability, and doctors will not face the financial burden associated with the payment of compensation. The aim of the scientific article is to develop proposals for successful implementation of this system and improvement of legislation. The legal review of this type of insurance is presented, the peculiarities of normative regulation of professional liability insurance of medical workers are studied. To achieve this goal, the authors analyze new legislative initiatives, changes and amendments in the current legislation, draw conclusions and proposals.